Supervisors’ Strategies to Facilitate Work Functioning among Employees with Musculoskeletal Complaints: A Focus Group Study - Tove Ask; Liv Heide Magnussen (The Scientific World Journal)
Aim. To explore what strategies the supervisors found beneficial to prevent or reduce sickness absence among employees with musculoskeletal complaints. Methods. Five focus groups were conducted and 26 supervisors from health and social sector participated. Commonly used strategies to prevent sickness absence and interdisciplinary cooperation in this work were discussed in the focus groups. Systematic text condensation was used to analyse the data. Results. The supervisors described five strategies for sick leave management: (1) promoting well-being and a healthy working environment, (2) providing early support and adjustments, (3) making employees more responsible, (4) using confrontational strategies in relation to employees on long-term sick leave, and (5) cooperation with general practitioners (GPs). Conclusions. Strategies of promoting a healthy working environment and facilitating early return to work were utilised in the follow-up of employees with musculoskeletal complaints. Supportive strategies were found most useful especially in the early phases, while finding a balance between being supportive, on one side, and confronting the employee, on the other, was endeavoured in cases of recurrent or long-term sick leave. Further, the supervisors requested a closer cooperation with the GPs, which they believed would facilitate return to work.